JUDUL ARTIKEL PENGARUH PROMOSI HARGA DAN SOCIAL MEDIA RECOMMENDATION KEPADA KEPUTUSAN PEMBELIAN KONSUMEN TERHADAP PRODUK DENGAN E-WOM NEGATIF: PERAN TIME PRESSURE SEBAGAI VARIABEL MODERASI (Studi Kasus pada Pelanggan E-Commerce di Wilayah Jawa Tengah) - Gusti Arrasyid, Pramudya Saelando; Yoestini, Yoestini (Diponegoro Journal of Management, 2024)
ABSTRACT In this modern era, commonly known as the digital age, information can easily and rapidly be disseminated through internet technology. The advancement of the internet has made everything more convenient, such as shopping. In this era, with just a mobile device and internet connection, we can shop anywhere and anytime we want. This convenience is made possible by the emergence of online buying and selling platforms, commonly referred to as E-commerce. However, with the convenience comes potential negative effects. Consumers now have an easier way to assess the quality of products or services through feedback and reviews available on E-commerce platforms. Prospective buyers can access these reviews, which can impact sellers with negative reviews struggling to sell their products. Sellers must employ marketing strategies to mitigate the impact of negative reviews, so that potential buyers can trust them and the products they offer. This research aims to assist sellers in understanding and analyzing the influence of marketing strategies, specifically price promotion, time pressure, and social media recommendations. With these three variables, the researcher investigates whether they can influence purchase decisions for products with negative electronic word-of-mouth (EWOM). The sample selection technique used is nonprobability sampling with purposive sampling as the method. The study utilizes 100 respondents who are residents of Central Java and customers of one of the E-commerce platforms in Indonesia. Data is collected through online questionnaires using Google Form. The research proposes three hypotheses, which are analyzed and tested using the Structural Equation Model (SEM) technique with Partial Least Squares (PLS) version 3. The results of testing the three proposed hypotheses indicate that all three hypotheses are supported. Specifically, price promotion has a positive and significant influence on purchase decisions. Time pressure has a positive and significant moderating effect on the relationship between price promotion and purchase decisions. Lastly, social media recommendations have a positive and significant impact on purchase decisions